‘You don’t respect me, but I’m worthy of respect’. Paramilitaries’ prison experience and conflict transformation in Colombia - Ariza, Libardo José (Punishment & society, 2019)
Through the case study of demobilised paramilitaries in Colombia, this article seeks to discuss how former combatants’ identities and perspectives are shaped by specific prison conditions, as well as the consequences of these vis-à-vis the fulfilment of transitional justice’s general goals of the reintegration of ex-combatants and peace-building. Former combatants incarcerated in facilities lacking minimum human rights standards, where State authority and legitimacy are weak, and where the precariousness of rehabilitation and re-entry programmes is manifest, have little opportunity of peacefully reintegrating into their communities and society. Under such conditions, ex-combatants adopt a discourse of resistance, which increases the risks of reoffending and rejoining illegal armed groups after release. This is not only counterproductive for peace-building and social reconciliation but it can also lead to the resumption of the armed conflict.